2011
DOI: 10.1007/s11205-011-9792-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Time Perspective in Greek Young Adults: Validation of the Zimbardo Time Perspective Inventory and Relationships with Mental Health Indicators

Abstract: In this article we examine the factorial structure of the Greek version of the Zimbardo Time Perspective Inventory (ZTPI; Zimbardo and Boyd in J Personal Soc Psychol 77:1271-1288, in a sample of 337 university students, using principal axis factoring (PAF) with oblique rotation, and its dimensionality using parallel analysis. Moreover, we evaluate the internal consistency reliability, the convergent validity (through associations with mental health indicators such as dispositional optimism, self-esteem, trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 39 publications
(32 reference statements)
11
81
0
11
Order By: Relevance
“…Whereas in approach acceptance, a person believes in death as a gateway to a happy life hereafter (Neimeyer, 1994). So, this fi nding supported studies which showed PP as related to a strong sense of self-esteem and happiness, and low levels of depression and anxiety (Anagnostopoulos & Griva, 2012). Present-Hedonistic (PH) showed positive correlations with escape and avoidance acceptance.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Whereas in approach acceptance, a person believes in death as a gateway to a happy life hereafter (Neimeyer, 1994). So, this fi nding supported studies which showed PP as related to a strong sense of self-esteem and happiness, and low levels of depression and anxiety (Anagnostopoulos & Griva, 2012). Present-Hedonistic (PH) showed positive correlations with escape and avoidance acceptance.…”
Section: Discussionsupporting
confidence: 76%
“…Studies showed that negative perception of the past refl ects an unhappy view toward the past and it is associated with depression, trait anxiety and self-reported unhappiness Anagnostopoulos & Griva, 2012). In additional, higher levels of depression and anxiety were also predicted by PN in individuals diagnosed with chronic diseases such as diabetes (Anagnostopoulos & Griva, 2012). Death is feared for different reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way in which an individual emotionally focuses on one aspect of time (e.g., past, present, or future) relative to other aspects of time, impacts that individual's daily decisions, behaviors, and plans . For example, individuals who tend to focus on the present are more likely to self-report substance use (Keough, Zimbardo, & Boyd, 1999;Wills, Sandy, & Yaeger, 2001), but those who focus on the future are more likely to engage in proactive coping (Anagnostopoulos & Griva, 2012). The relation between temporal orientation and health-related outcomes may be moderated by an individual's desire for control over the situation (Fieulaine & Martinez, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…asimismo, ha sido adaptado a otros idiomas para su uso con poblaciones de otras nacionalidades como la española (Díaz-Morales, 2006), mexicana (Corral-Verdugo, FraijoSing y Pinheiro, 2006), brasileña (Milfont, Andrade, Belo y Pessoa, 2008), portuguesa (Ortuño y Gamboa, 2009), francesa (Apostolodis y Fieulaine, 2004), italiana (D'Alessio, Guarino, de Pascalis, y Zimbardo, 2003) y griega (Anagnostopoulos y Griva, 2012), entre otras, cuyos resultados han mostrado que salvo matices y leves variaciones de tipo sociocultural, la estructura factorial original y propiedades del instrumento pueden mantenerse.…”
Section: Introductionunclassified